The use requirement for trademarks: a comparative study of the French, European Union trademark and United States federal laws - Pras, Matthieu (fi=Turun yliopisto|en=University of Turku|, 2016)
The French and the European Union (EU) trademark laws have been largely harmonized and therefore share common principles and rules, which strikingly contrast with those of United States (US) federal law. Importantly, EU law makes property depend on simple registration whereas the US law approach is grounded on the notion of use. Yet, the requirement of use for maintaining trademark protection is a common feature in all three systems. Proper to trademark law, its theoretical justification may seem unclear. It is proposed that adopting a use requirement rests on reasons pertaining to the nature and the functions of trademarks. On the one hand, the trademarks’ nature of exclusive rights over pieces of market language justifies the use requirement as a means to temper easily acquired property rights in registration systems such as those in the EU and to regulate the monopolization of valuable pieces of market language in general. On the other hand, use is the obvious condition for trademarks to perform their functions assigned by law. The constructions of the use requirement for French and EU trademarks, on the one hand, and for US federal trademarks on the other hand are presented and compared. Substantial implementation aspects are then analyzed from the point of view of each jurisdiction, including the personal, the material and the spatiotemporal temporal aspects, as well as the limitations to the requirement. The aspects in French and EU law are compared to those in US law, trying to detect what could enhance EU law.